Personalized pricing with heterogeneous mismatch costs - Noriaki Matsushima; Tomomichi Mizuno; Cong Pan (Osaka University, Institute of Social and Economic Research (ISER), 2022)
Personalized pricing has become a reality through digitization. We examine firms' incentives to adopt one of the three pricing schemes: uniform, personalized, or group pricing in a Hotelling duopoly model. There are two types of consumer groups that are heterogeneous in their mismatch costs. We show that both firms employ personalized pricing in equilibrium regardless of the heterogeneity of consumer groups. If the consumer groups' heterogeneity is significant, the profits are higher when both firms use personalized pricing than when they employ uniform pricing; otherwise, the latter profits are higher than the former. Profits are highest when firms employ group pricing among the three cases. The ranking of consumer welfare among the three cases is opposite to that of profits.
Keywords: L13; D43; 330; Personalized pricing; Group pricing; Heterogeneous consumer types; Hotelling model